ØªÙÙÙÙ Ø§ÙØªØ±Ø§Ø« Ø§ÙØØ¶Ø±Ù Ø§ÙØªØ§Ø±ÙØ®Ù ÙØ¢ÙÙØ© ÙØªØÙÙÙ Ø§ÙØªÙÙÙØ© Ø§ÙÙØ³ØªØ¯Ø§ÙØ© Ø¨ÙØ¯ÙÙØ© ØªØ¨Ø³Ø© - ØØ¬ÙØ©, Ø§ÙØ£Ø³ØªØ§Ø°: Ø¹ÙÙØ; Ø§ÙÙØ§Ø¯Ù ÙØ¹Ø±ÙÙ, Ø§ÙØ£Ø³ØªØ§Ø° Ø§ÙØ¯ÙØªÙØ± ÙØÙØ¯ Ø (Sciences de l'Homme et de la SociÃ©tÃ©, 2015)
ÙØ´ÙÙ Ø§ÙØªØ±Ø§Ø« Ø§ÙØ¹ÙØ±Ø§ÙÙ Ø·Ø§ÙØ© ÙØ§ÙÙØ© ÙÙÙÙ Ø§Ø³ØªØºÙØ§ÙÙØ§ Ø«ÙØ§ÙÙÙØ§ ÙØ³ÙØ§ØÙÙØ§Ø ÙÙÙØ§ ÙØ§ Ø´Ù ÙÙÙ Ø£Ù ÙØ·Ø§Ø¹ Ø§ÙØ³ÙØ§ØØ© Ø£Ø¯Ø§Ø© ÙØ¹Ø§ÙØ© ÙÙ Ø§ÙØªÙÙÙØ© Ø§ÙÙØÙÙØ© Ø§ÙØ·ÙØ§ÙÙØ§ ÙÙ ÙÙÙØ²Ø§ØªÙ Ø§ÙØªÙ ÙÙØ§ Ø¹ÙØ§ÙØ© Ø¨Ø§ÙØ§ÙØªØµØ§Ø¯ Ø§ÙØ¬Ø²Ø¦Ù ÙØ§ÙØ±Ø¨Ø ÙØ§ÙØ³ÙÙÙØ©Ø ÙØ¥Ø¯Ø±Ø§ÙÙØ§ ÙÙØ§ ÙØ£ÙÙÙØ© Ø§ÙØªØ±Ø§Ø« Ø§ÙØªØ§Ø±ÙØ®Ù ÙØ§ÙØ«ÙØ§ÙÙ Ø§ÙÙØ§Ø¯Ù ÙÙ Ø§ÙÙÙÙØ¶ Ø¨Ø§ÙÙØ´Ø§Ø· Ø§ÙØ³ÙØ§ØÙ Ø¹ÙÙ ÙØ³ØªÙÙ ÙØ¯Ù Ø§ÙØ¨ÙØ§Ø¯ ÙØ¯ÙØ±Ù ÙÙ Ø¨Ø¹Ø« ØªØÙÙØ§Øª Ø§Ø¬ØªÙØ§Ø¹ÙØ© ÙØ§ÙØªØµØ§Ø¯ÙØ© ØªØ´ÙÙ ÙÙ ØØ¯ Ø°Ø§ØªÙØ§ ÙØ§Ø¹Ø¯Ø© Ø§ÙØªÙÙÙØ© Ø¹ÙÙ Ø§ÙÙØ³ØªÙÙ Ø§ÙÙØÙÙØ ÙØ¨Ø§ÙØªØ§ÙÙ ØªÙØ¹ÙÙ ÙØ´Ø§Ø· Ø£Ø³Ø§Ø³Ù ÙØ¯Ø± ÙÙØ£Ø±Ø¨Ø§Ø ÙØ¨Ø·Ø±ÙÙØ© ÙØ³ØªØ¯ÙÙØ© ÙØ«Ø±ÙØ© ÙØ§ ØªÙØ¶Ø¨Ø ØªØ£ØªÙ Ø¯Ø±Ø§Ø³ØªÙØ§ Ø§ÙÙØ§Ø¯ÙØ© Ø§ÙÙ ØªÙÙÙÙ Ø§ÙØªØ±Ø§Ø« Ø§ÙØØ¶Ø±Ù ÙØ¢ÙÙØ© ÙÙ Ø¢ÙÙØ§Øª Ø¨Ø¹Ø« Ø§ÙÙØ´Ø§Ø· Ø§ÙØ³ÙØ§ØÙ ÙØªØÙÙÙ ØªÙÙÙØ© ÙØ³ØªØ¯ÙÙØ© ÙÙ ÙØ¯ÙÙØ© Ø¹Ø±ÙÙØ© ÙÙØ¯ÙÙØ© ØªØ¨Ø³Ø©.Â  Â  Abstract : Urban heritage is a potential can be exploited in the areas of culture and tourism, and no doubt that the latter is an efficient tool for local development from its characteristics related to microeconomics and liquidity, and aware of the importance of historical and cultural heritage in the promotion of tourist activities in cities across the country, and its role in the resurrection of the social and economic changes, in themselves constitute a development database locally, that is to origin of the generator core business profits in a sustainable manner, as an inexhaustible resource, our study aimed to come evaluation of urban heritage as a mechanism for the recovery of tourist activity, and achieving sustainable development in an ancient city like Tebessa, she led us to study the history of the town of Tebessa.